Strategi Promosi Pariwisata Pada Kawasan Wisata Mangrove Pendopo Teritip, Kelurahan Teritip, Kecamatan Balikpapan Utara - Boby Mugi Pratama; Hendy Indrawan Sunardi; Siti Indreani; Dian Puspitasari; Putu Septa; Rut Nauli Hosana; Shoffi Akmalunnisaa; Richard Chandra Tjiang (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2022)
Improving the community's economy and national energy security are the main focus in the utilization of regional potential in the city of Balikpapan. As a form of contribution from educational institutions in this regard, Kalimantan Institute of Technology (ITK) held a program to improve the quality of natural resources and human resources in Kelurahan Teritip, Balikpapan City, which was stated in Program Mahasiswa Mengabdi Desa (PMMD). The problem faced by the Mangrove Pendopo Teritip in Kelurahan Teritip is the unavailability of adequate markers that indicate if at that location there is a mangrove tourism spot, thus making the Mangrove Pendopo Teritip unknown to visitors who are not from the surrounding area. The solution that has been implemented is to use digital promotions using advertisements on online platforms such as Instagram with the destination of Mangrove Pendopo Teritip tourism in Kelurahan Teritip, which can be known by wider community, especially the people of Balikpapan. Then also made a direction marker that leads to the Mangrove Pendopo Teritip tourism with the aim of being able to help and make it easier for people from outside the area to find the tourist location of this Mangrove Pendopo Teritip. In addition, a program for making both thematic maps of tourist sites and mangrove education information boards was also carried out so that they could serve as informative messages for tourists. The program was implemented in a period of approximately 12 weeks.